2011
DOI: 10.12968/ijpn.2011.17.9.440
|View full text |Cite
|
Sign up to set email alerts
|

The practice of withholding and withdrawing life-support measures among patients with cancer in Jordan

Abstract: In Jordan, an Arabic Islamic country, decisions around withholding and/or withdrawing life support measures still present both moral and professional dilemmas. The purpose of this study was to explore the use of such measures among patients with cancer in Jordan. The medical records of 436 patients with cancer who were at least 18 years old and who died at a specialized cancer centre in Jordan in 2008 were reviewed retrospectively. Of those, 212 (48.6%) had a written decision to withhold or withdraw life suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…It was reported that critically ill patients with malignancy or ultimately fatal underlying diseases were more likely to have their life-sustaining therapy withheld or withdrawn than those without malignancy or fatal diseases [15][16]. A study of a specialized cancer center in Jordan demonstrated a high proportion (48.6%) of adult cancer patients making decisions to withhold or withdraw life support measures [17], which was even higher than the result of our center.…”
Section: Discussionmentioning
confidence: 57%
“…It was reported that critically ill patients with malignancy or ultimately fatal underlying diseases were more likely to have their life-sustaining therapy withheld or withdrawn than those without malignancy or fatal diseases [15][16]. A study of a specialized cancer center in Jordan demonstrated a high proportion (48.6%) of adult cancer patients making decisions to withhold or withdraw life support measures [17], which was even higher than the result of our center.…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, it is suggested that the in-service education office in hospitals focuses more on this topic. In addition, Jordanian legal guidelines and policies to assist healthcare providers in their decisions in the area of palliative care are absent (Khater et al, 2011). Therefore, clear legal guidelines and policies should be established in Jordan regarding the provision of ANH.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that nurses have insufficient information about the ANH potential complications such as worsening of peripheral oedema, aspiration pneumonia, intestinal ischaemia and catheter sepsis (Hiesmayr, 2012; Morita et al, 2005). Other studies found that despite nurses' perceptive that ANH cannot prolong a patient's life or improve the quality of life or mental status, they still believe in the importance of providing all supportive measures for patients with advanced cancer (Ke et al, 2008a; Khater et al, 2011; Stiles, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Keeping them on mechanical ventilation will increase their pain and slow their death rather than letting them die in peace and dignity (Khan, 1986;Khater, 2011).…”
Section: End Of Lifementioning
confidence: 99%